An assessment of the effectiveness of in-situ signage in multiple-use marine protected areas in providing information to different recreational users. (June 2015) - Martin, Carol L.; Momtaz, Salim; Jordan, Alan; Moltschaniwskyj, Natalie A.
Abstract: In-situ signage is a cost effective environmental education tool used in marine protected area (MPA) management, and the design and location of signage is crucial to attract the attention of targeted audiences. The implementation of multiple-use MPAs increases the challenges of communicating awareness of MPA boundaries and permitted activities. Currently, little is known about how effective signage in multiple-use MPAs is in communicating information to stakeholders that will promote supportive attitudes and behaviours towards MPAs. This study evaluated the usefulness of in-situ signage in an existing multiple-use MPA, to determine if signs pertaining to the MPA captured the attention of recreational users, and provided adequate information. Structured interviews with recreational fishers, divers, and other users, were used to determine users׳ awareness of being in an MPA, their awareness of management objectives and associated zoning scheme, together with levels of agreement or disagreement on whether or not current in-situ signage adequately communicates information about the MPA. It was evident that the types and accessibility of in-situ signs in the MPA may not be effective at capturing the attention of intended audiences and providing relevant information, with the exception of signs located at the dive site, due to their design, size, and placement. Awareness differed among the three user groups, together with their views on the effectiveness of signage. Many recreational fishers believed existing signage was inadequate and unclear, and expressed frustrations with the complexity of zoning rules and location of their boundaries. Based on this study, recommendations about the presentation, content, and placement of signage relative to access points, and information required by MPA users, is provided.